Superinfected Cystic Omental Lymphangioma: A Rare Cause of Acute Abdomen in Children - Alazar Wogayehu Gebrehana; Wondwosen Mengist Dereje; Nestanet Gete Kasawudeg; Andualem Getie Alemahu; Belete Chaklu; Mesfin Tesera Wassie; Bethlehem Aliye Asfaw (Clinical Case Reports)
ABSTRACT Cystic lymphangioma is a benign yet rare vascular anomaly with an estimated incidence rate of 1 in every 20,000–250,000 individuals. They often tend to be asymptomatic. Lymphangiomas are usually diagnosed in children under 2 years of age and typically present as a lateral neck or axillary mass. Their presentation as an abdominal mass with acute abdominal presentation is unusual. In this case report, we present a case of cystic omental lymphangioma in a 9‐year‐old male schooler who was presented with sudden onset of severe, sharp lower abdominal pain lasting 4 days. The patient had a previous history of similar abdominal complaints, where he received treatment for intestinal parasites without significant improvement. Imaging and histopathology results later found a cystic omental lymphangioma which was treated successfully with surgical resection. We also navigate challenges associated with the early diagnosis of omental lymphangiomas in resource‐limited settings.